2006
DOI: 10.1016/j.cyto.2006.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The lack of cardiotrophin-1 alters expression of interleukin-6 and leukemia inhibitory factor mRNA but does not impair cardiac injury response

Abstract: Cardiotrophin-1 (CT-1) was identified as a growth factor for cardiac myocytes, and CT-1 protects myocytes from cell death. Adult CT-1−/− mice exhibit neural deficits including the loss of preganglionic sympathetic neurons, but their autonomic and cardiac parameters have not been examined. We used these mice to determine if the absence of CT-1 or loss of preganglionic sympathetic input altered heart rate, left ventricular pressure, cardiac contractility (dP/dt), or cell death following ischemia-reperfusion. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
(76 reference statements)
0
17
0
1
Order By: Relevance
“…CT-1 administration resulted in decreased infarct size and reduced cardiomyocyte apoptosis in a rat model of myocardial ischemia and reperfusion [171]. However, CT-1 absence did not affect infarct size in a mouse model of reperfused infarction suggesting that endogenous CT-1 does not play an essential role in acute ischemic cardiac injury [172]. Prolonged CT-1 upregulation in the infracted myocardium may modulate the fibrotic response through effects on fibroblast proliferation [173].…”
Section: The Il-6 Family Of Cytokinesmentioning
confidence: 99%
“…CT-1 administration resulted in decreased infarct size and reduced cardiomyocyte apoptosis in a rat model of myocardial ischemia and reperfusion [171]. However, CT-1 absence did not affect infarct size in a mouse model of reperfused infarction suggesting that endogenous CT-1 does not play an essential role in acute ischemic cardiac injury [172]. Prolonged CT-1 upregulation in the infracted myocardium may modulate the fibrotic response through effects on fibroblast proliferation [173].…”
Section: The Il-6 Family Of Cytokinesmentioning
confidence: 99%
“…These results provide evidence that the CT-1 receptor is composed of a tripartite complex, a situation similar to the high affi nity receptor for ciliary neurotrophic factor 15 . Results indicate that gp130 plays a crucial role in myocardial development and hematopoiesis during embryogenesis 5,106 . Factors regulating CT-1 expression and regulated by CT-1 are presented in tables 1 and 2.…”
Section: Cardiotrophin-1 Receptormentioning
confidence: 99%
“…Saline control injections confirmed that the 20-l volume bolus dose did not trigger changes in arterial pressure or HR. In another set of mice, ganglionic block was established with hexamethonium, and increasing doses (4,8,16,32, and 64 g/kg, volumes: 5-20 l) of the ␤-agonist dobutamine were then administered. The next dose was injected as soon as the increasing HR leveled off.…”
mentioning
confidence: 99%
“…Ischemia-reperfusion was carried out as previously described (8). Adult mice were placed in an induction chamber and anesthetized with 4% isoflurane.…”
mentioning
confidence: 99%